2016
DOI: 10.1177/0361684315622645
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes About Gender and Science

Abstract: We conducted two studies and our primary goal was to assess the similarity between stereotypes about women and men and stereotypes about successful scientists. In addition, we examined the degree to which scientists, men, and women are seen as agentic or communal. Results revealed greater similarity between stereotypes about men and stereotypes about scientists than between stereotypes about women and scientists. Men and scientists were seen as highly agentic, women as highly communal, and scientists as less c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
2
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(214 citation statements)
references
References 66 publications
4
162
2
13
Order By: Relevance
“…Because people implicitly stereotype the ideal successful scientist or engineer as male [44,45,66], when it comes to giving credit to members of a science team in the absence of complete information, these implicit gender stereotypes subtly push evaluators to assume men on the team must have made more unique contributions than the women, absent clear markers of leadership. For similar reasons, expectation states theory would also predict that in masculine professions like STEM, evaluators often assume that men (more than women) are the intellectual leaders in the team whose contribution is critical to the team's discovery.…”
Section: Valuing Collaborationmentioning
confidence: 99%
“…Because people implicitly stereotype the ideal successful scientist or engineer as male [44,45,66], when it comes to giving credit to members of a science team in the absence of complete information, these implicit gender stereotypes subtly push evaluators to assume men on the team must have made more unique contributions than the women, absent clear markers of leadership. For similar reasons, expectation states theory would also predict that in masculine professions like STEM, evaluators often assume that men (more than women) are the intellectual leaders in the team whose contribution is critical to the team's discovery.…”
Section: Valuing Collaborationmentioning
confidence: 99%
“…As to psychological factors, when women enter male dominated professions, such as STEM fields, they are susceptible to stereotypes or bias (Hanson, ; Logel, et al, ). In particular, it has been well studied that gender stereotypes alone can hamper one's identity, efficacy, and performance, known as stereotype threat (Carli, Alawa, Lee, Zhao, & Kim, ; Good, Aronson, & Harder, ; Guimond & Roussel, ; Moss‐Racusin, Dovidio, Brescoll, Graham, & Handelsman, ; Stoet & Geary, ). Research found that those who were vulnerable to stereotype threats were likely to have a static rather than a growth perspective on their ability (Hill et al, ; Wang & Degol, ).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of research shows that STEM departments are different from non-STEM departments in terms of organizational demographics and the prevalence of gender role stereotypes. Women faculty and students comprise a numeric minority in STEM departments, and these disciplines tend to view men (more than women) as disciplinary experts (Carli et al 2016;Dasgupta and Stout 2014;Nosek et al 2002). Minority status and stereotypes associating scientific expertise with maleness contribute to an unsupportive climate for women faculty, reducing their professional satisfaction, and increasing their risk of attrition relative to male colleagues (Blackwell et al 2009;Callister 2006;Corley 2005;Fox 2010; Greene et al 2010;Hillard et al 2014;Xu 2008).…”
Section: Introductionmentioning
confidence: 99%